Antigenic assessment for the β2-glycoprotein I/Platelet factor 4 complex in thrombotic patients with antiphospholipid syndrome - Villani, Francesca; Capozzi, Antonella; Ucci, Federica Maria; Truglia, Simona; De Michele, Manuela; Mancuso, Silvia; Rapino, Luca; Tripodi, Giuseppe; Manganelli, Valeria; Riitano, Gloria; Misasi, Roberta; Sorice, Maurizio; et al. (Frontiers in Immunology, 2026)
ObjectiveAntiphospholipid syndrome (APS) is an autoimmune condition characterized by recurrent thrombosis, pregnancy-related complications and circulating antiphospholipid antibodies, including anti-β2-glycoprotein I (β2-GPI). Platelet factor 4 (PF4) is a pro-coagulant protein expressed by activated platelets. It is considered a potential platelet ligand for oxidized β2-GPI, and this interaction may play a role in the thrombotic manifestations of APS. This study aims to assess β2-GPI/PF4 complex autoantibodies in sera of thrombotic patients with APS and their potential functional role in platelet activation.MethodsWe analysed sera from 73 patients with thrombotic APS, 20 with obstetric APS, 20 with systemic lupus erythematosus (SLE), 20 with non-APS thrombosis, 3 with vaccine-induced immune thrombotic thrombocytopenia (VITT), 20 with COVID-19 and 45 healthy donors (HDs). These samples were tested by ELISA for antibodies to the β2-GPI/PF4 complex after in vitro induction of spontaneous β2-GPI protein oxidation.ResultsAnti-β2-GPI/PF4 were detected in 34.24% of thrombotic APS patients and 20% of obstetric APS. All VITT and none of the SLE, non-APS thrombosis, COVID-19 patients and HDs were positive for anti-β2-GPI/PF4. In thrombotic APS, a significant association was found between anti-β2-GPI/PF4 positivity and antibody titer with venous thrombotic complications (p = 0.032, p = 0.01) as well as between anti-β2-GPI/PF4 and triple positivity to conventional aPLs (p = 0.028). Notably, antibody titer correlated with the young age both at diagnosis (p<0.001) and at the current evaluation (p=0.001). Moreover, HDs’ platelets, in vitro treated with Ig fractions from APS patients, exhibited a significant increase in phospho-ERK and phospho-p38 expression, leading to NF-κB activation and TF expression.ConclusionThis study demonstrated the presence of anti-β2-GPI/PF4 in patients with APS, where it may be involved in the mechanism underlying the hypercoagulable state and correlated with a greater risk of developing thrombosis, especially in the young population.